A Tale of Two Visions: Hegemonic Whiteness and Bilingual Education. (January 2016) - Flores, Nelson
In this article, I examine two visions of bilingual education that emerged during the Civil Rights Movement: race radicalism and liberal multiculturalism. I argue that although proponents of both visions believed that bilingual education was necessary for empowering language-minoritized populations, race radicalism conceptualized this empowerment as liberation from hegemonic Whiteness while liberal multiculturalism conceptualized this empowerment as assimilation into hegemonic Whiteness. I then examine the ways that the institutionalization of bilingual education erased race radicalism through reframing the debate around whether these programs should be subtractive or additive. I conclude by arguing that this dominant framing of bilingual education debates continues to reproduce hegemonic Whiteness in ways that marginalize language-minoritized students.